Improving Self-Efficacy for Weight Loss Management in a Group Setting - Carlton, Felice (My University, 2017)
Problem Statement: The growing costs of managing chronic disease in the United States is exacerbated by the obesity epidemic; obesity often contributes to increased comorbidities, or worsens the progression of existing chronic disease (Smith & Wroth, 2011). Purpose: The purpose of the scholarly project was to improve self-efficacy for the purpose of weight loss management in a group setting. Methods: A descriptive project involving a pre-assessment and a post-assessment questionnaire of self-efficacy related to weight loss behavioral change was used. A voluntary six-week weight loss group program occurred in a rural community’s health department. The target group included adult residents 18-years-old or older who received care through the health department, and adult health department employees who desired to lose weight. Candidates were recruited by choosing to participate in the project after receiving flyers distributed by the health department. At the first session, the participants were asked to complete an initial weight efficacy lifestyle questionnaire (WEL-SF); and to select an identifier that was used track attendance and WEL-SF pre and post-assessments. The facilitator did not collect any identifying information during the program. The participants established a feasible weight loss behavioral goal that they worked towards during the program. The participants completed the WEL-SF assessments at weeks one, four, and five; and a post-assessment on week six as an ongoing evaluation of their weight efficacy lifestyle behaviors. Outcome measures included: the participants’ attendance to the program, the pre and post lifestyle questionnaire data, and the participants self-report of whether they met or made progress towards their goal. Significance: Improved weight-loss behaviors through improved participants’ self-efficacy was facilitated through weekly health coaching sessions. The long-term impacts have the possibility of improving well-being and decreasing health care costs (Armstrong et al., 2013).
n/a
Keywords: weight loss; health coach; integrative health coaching; self-efficacy